2014
DOI: 10.1073/pnas.1319353111
|View full text |Cite
|
Sign up to set email alerts
|

Exchange of ADP with ATP in the CII ATPase domain promotes autophosphorylation of cyanobacterial clock protein KaiC

Abstract: The cyanobacterial circadian oscillator can be reconstituted in vitro. In the presence of KaiA and KaiB, the phosphorylation state of KaiC oscillates with a periodicity of ∼24 h. KaiC is a hexameric P-loop ATPase with autophosphorylation and autodephosphorylation activities. Recently, we found that dephosphorylation of KaiC occurs via reversal of the phosphorylation reaction: a phosphate group attached to Ser431/Thr432 is transferred to KaiC-bound ADP to generate ATP, which is subsequently hydrolyzed. This unu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 26 publications
6
50
3
Order By: Relevance
“…At the beginning of the nanocomplex cycle, KaiA rapidly interacts intermittently with the CII tentacles of KaiC 5962 . This transient interaction stimulates the phosphorylation of KaiC (or inhibits dephosphorylation, thereby shifting the reaction towards phosphorylation) 57,58,63 , and when S431 of KaiC achieves the (T432/pS431) state in the phosphorylation sequence, KaiB binds to KaiC. A recent study reported that KaiB exists in two diametrically different conformations: a ground state (gsKaiB) that does not interact readily with KaiC, and a substantially fold-shifted state (fsKaiB) that binds to the CI domain 18 (FIG.…”
Section: Timekeeping Mechanisms In Cyanobacteriamentioning
confidence: 99%
“…At the beginning of the nanocomplex cycle, KaiA rapidly interacts intermittently with the CII tentacles of KaiC 5962 . This transient interaction stimulates the phosphorylation of KaiC (or inhibits dephosphorylation, thereby shifting the reaction towards phosphorylation) 57,58,63 , and when S431 of KaiC achieves the (T432/pS431) state in the phosphorylation sequence, KaiB binds to KaiC. A recent study reported that KaiB exists in two diametrically different conformations: a ground state (gsKaiB) that does not interact readily with KaiC, and a substantially fold-shifted state (fsKaiB) that binds to the CI domain 18 (FIG.…”
Section: Timekeeping Mechanisms In Cyanobacteriamentioning
confidence: 99%
“…It has been experimentally suggested that the change of the ADP/ATP exchange in C2 induces an equilibrium shift toward (de)phosphorylated states of C2 [16]. The present model designs the sequential phosphorylation of C2 as schematically shown in Fig.…”
Section: Model Setupmentioning
confidence: 99%
“…Moreover, we assume that KaiA can bind to C2 only when C2 is in the exposed state. To realize the experimental result that KaiA facilitates the ADP/ATP exchange in C2 [16], we also assume that the ADP/ATP exchange in C2 is allowed only in the exposed state. With these assumptions, the KaiA binding promotes the ADP/ATP exchange through the stabilization of the exposed state, i.e.…”
Section: Model Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The former are composed of kinase, phospho-transferase (ATP synthase (47,48)), and ATPases in CII and CI. KaiB may modulate phosphorylation, dephosphorylation, or ATP hydrolysis, or perhaps influence the ratio between bound ADP and ATP (49). Because of the rotational symmetry of the KaiC particle (Fig.…”
mentioning
confidence: 99%